Avaliação de língua inglesa nos anos iniciais do ensino fundamental: contribuições da prática de professores em serviço - Oliveira, Thiago Alcebíades (Universidade Federal de São Carlos, 2026)
Despite the growing body of research in the field of language education with children, studies on assessment in this context tend to emerge largely from issues and needs identified in teaching practice (Quevedo-Camargo and Tonelli, 2024). In that regard, this research aims at analyzing assessment practices of English language teachers in the early years of elementary education in the municipal school system of Ribeirão Preto/SP regarding Assessment for Learning (AfL) (Earl, 2003), language education with children (Rocha, 2008; Santos, 2011; Tonelli, 2023), and language assessment literacy (Scaramucci, 2006; Quevedo-Camargo, 2020) principles. This is an interpretivist qualitative study, with data generated through interviews and questionnaires with in-service teachers. The results indicate that assessment practices are organized based on the continuous observation of students’ participation, engagement, and productions, integrating into everyday pedagogical practice. Such practices show approximations with AfL, especially in monitoring the process, although in a non-systematized manner and mediated by institutional conditions. Assessment literacy proves to be heterogeneous, constructed through experience and marked by the coexistence of different conceptions of assessment. It is concluded that assessment is configured as a situated process, shaped by contextual and formative demands.
English language assessment in the early years of elementary education: contributions from the practice of in-service teachers
Keywords: Avaliação para Aprendizagem; Letramento em Avaliação de Línguas; Educação Linguística em Inglês com Crianças; Anos Iniciais do Ensino Fundamental; Práticas Avaliativas; Assessment for Learning; Language Assessment Literacy; Language Education in English with Children; Primary Education; Assessment Practices; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUAS ESTRANGEIRAS MODERNAS; 4. Educação de Qualidade